2022
DOI: 10.3389/fnut.2022.854725
|View full text |Cite
|
Sign up to set email alerts
|

Slowly Digestible Carbohydrate Diet Ameliorates Hyperglycemia and Hyperlipidemia in High-Fat Diet/Streptozocin-Induced Diabetic Mice

Abstract: ObjectiveGiven that the prevalence rate of type 2 diabetes mellitus (T2DM) continues to increase, it is important to find an effective method to prevent or treat this disease. Previous studies have shown that dietary intervention with a slowly digestible carbohydrate (SDC) diet can improve T2DM with almost no side effects. However, the underlying mechanisms of SDC protect against T2DM remains to be elucidated.MethodsThe T2DM mice model was established with a high-fat diet and streptozocin injection. Then, SDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(64 reference statements)
1
4
0
Order By: Relevance
“…68 Furthermore, a recent research demonstrated that a diet supplemented with slowly digestible carbohydrates improved serum glycemic and lipid profiles in diabetic mice, accompanied by an elevation in Desulfovibrio abundance. 69 In line with these findings, our study revealed a positive correlation between the Desulfovibrio abundance and the fecal content of valeric acid, cholesterol, dehydrocholesterol, total neutral sterols, and lithocholic acid (Fig. 5).…”
Section: Food and Function Papersupporting
confidence: 86%
“…68 Furthermore, a recent research demonstrated that a diet supplemented with slowly digestible carbohydrates improved serum glycemic and lipid profiles in diabetic mice, accompanied by an elevation in Desulfovibrio abundance. 69 In line with these findings, our study revealed a positive correlation between the Desulfovibrio abundance and the fecal content of valeric acid, cholesterol, dehydrocholesterol, total neutral sterols, and lithocholic acid (Fig. 5).…”
Section: Food and Function Papersupporting
confidence: 86%
“…One such study highlighted the protective role of DSV in NAFLD via its production of acetic acid [ 127 ]. In a recent study, supplementation with a slowly digestible carbohydrate diet improved hyperglycemia and hyperlipidemia in high-fat diet-streptozocin-induced diabetic mice, resulting in an increase in DSV population [ 128 ]. However, the role of DSV in these studies is not clear, and further research demonstrating a direct role of DSV in the development of metabolic syndrome is needed.…”
Section: Dsv and Diseasesmentioning
confidence: 99%
“…It has been shown that a diet high in refined or processed starches and sugars that have lost the majority of fibers (~40% insoluble dietary fiber) and nutrition value can produce substantial swings in blood glucose and insulin levels, 23,24 proceed TG accumulation, the key driver of central obesity triggering adipocytokine dysregulation, and generation of inflammation, IR, MetS, and cardio‐metabolic complications 25,26 . On the other hand, complex CHO, that is, slowly digestible, such as whole grain, bran, as well as nondigestible and lente CHO have been shown to improve postprandial insulinemia, gut satiety peptides, gut microbiota, hyperlipidemia, lean body mass, inflammation and, ultimately, lower the prevalence of MetS and T2DM 27–30 . Recently short‐chain fatty acids (SCFAs) derived from dietary fibers have been used as potential therapeutic targets in the management of various metabolic disorders 27–31 .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 On the other hand, complex CHO, that is, slowly digestible, such as whole grain, bran, as well as nondigestible and lente CHO have been shown to improve postprandial insulinemia, gut satiety peptides, gut microbiota, hyperlipidemia, lean body mass, inflammation and, ultimately, lower the prevalence of MetS and T2DM. [27][28][29][30] Recently short-chain fatty acids (SCFAs) derived from dietary fibers have been used as potential therapeutic targets in the management of various metabolic disorders. [27][28][29][30][31] For example, SCFAs (acetate, propionate, and butyrate) are the main metabolic products of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation